The Effect of Advertising, Sales Promotion, Personal Selling and Brand Image on the Purchase Decision of Honda PCX Motorcycle in Surabaya - Zulkarnain Aji Putra; I Gede Arimbawa (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose:. This study aims to analyze the effect of advertising, sales promotion, personal selling and brand image on purchasing decisions for Honda PCX motorcycles in the city of Surabaya.